2021
DOI: 10.1186/s12864-020-07333-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-imbalanced conditions shift the interplay between zooplankton and gut microbiota

Abstract: Background Nutrient stoichiometry of phytoplankton frequently changes with aquatic ambient nutrient concentrations, which is mainly influenced by anthropogenic water treatment and the ecosystem dynamics. Consequently, the stoichiometry of phytoplankton can markedly alter the metabolism and growth of zooplankton. However, the effects of nutrient-imbalanced prey on the interplay between zooplankton and their gut microbiota remain unknown. Using metatranscriptome, a 16 s rRNA amplicon-based neutra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Therefore, using LEfSe analysis, we identified a shift in the indigenous microbiota due to storage conditions without artificial contamination ( Figure 5 ). In general, a higher absolute LDA value indicated that the species were more enriched in the group [ 46 ]. We found that Pantoea (c), Serratia (d), Pseudomonas (e; affiliated to the Pseudomonadaceae family within the Pseudomonadales order), and Stenotrophomonas (h; affiliated to the Xanthomonadaceae family within the Xanthomonadales order) at the genus level were significantly enriched in the unwashed group stored at 4 °C (LDA score ≥ 4.0; p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, using LEfSe analysis, we identified a shift in the indigenous microbiota due to storage conditions without artificial contamination ( Figure 5 ). In general, a higher absolute LDA value indicated that the species were more enriched in the group [ 46 ]. We found that Pantoea (c), Serratia (d), Pseudomonas (e; affiliated to the Pseudomonadaceae family within the Pseudomonadales order), and Stenotrophomonas (h; affiliated to the Xanthomonadaceae family within the Xanthomonadales order) at the genus level were significantly enriched in the unwashed group stored at 4 °C (LDA score ≥ 4.0; p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…GMC plays an important role in the physiology performance (e.g., fitness, growth, survival, and reproduction) of zooplankton host and greatly influences the biogeochemical cycles in the ocean (Roura et al, 2017;Callens et al, 2018;Li et al, 2021). Therefore, disentangling the major factors regulating the spatiotemporal dynamics of GMC in zooplankton remains a key issue in recent studies.…”
Section: Copepod Gmc Should Be Studied At the Individual Levelmentioning
confidence: 99%
“…These MP effects on the grazer's gut may have reverse effects on ocean productivity. 141,158 Overall, phytoplankton interactions with MP and PL have direct and indirect impacts on zooplankton and the higher trophic states with profound consequences for predator fitness and survival.…”
Section: Bottom-up and Top-down Impactsmentioning
confidence: 99%
“…Thus, they form niches facilitating accelerated microbial evolution in the plastisphere through horizontal gene transfer of potentially hazardous genes such as antibiotic resistance genes . They may also constitute “future sinks” of pathogenic and/or invasive microorganisms and pollutants which potentially affect human and ecosystem health. , It is also important to note that ingestion of these pathogenic and pollutant-laden MP, and the potential desorption of MP pollutants under low pH conditions, e.g., in the gut of zooplankton and fish, will have devastating consequences on higher trophic levels and even humans. …”
Section: Is the Phytoplankton Community Resilient To Omnipresent Mp A...mentioning
confidence: 99%
See 1 more Smart Citation